Using Concept Mapping to Enhance Reception and Setting Skills of Students with Autism at Al-Sabtain Academy - Landah Mhmood Dawood, (Musamus Journal of Physical Education and Sport (MJPES), 2025)
This study examined the effect of using the concept mapping strategy in teaching the skills of reception and preparation in volleyball for students at Al-Sabtain Academy for Autism. The idea of the research came from the need to apply modern teaching methods that help students connect and organize information instead of only receiving it. The study aimed to prepare educational units based on concept mapping and to identify their effect on learning these skills. The researcher used the experimental method with two similar groups, applying pre- and post-tests to measure the development of performance. The participants were chosen from students enrolled at the academy. After analyzing the data, the results showed a clear improvement in the students’ level of learning and performance for both reception and preparation skills. The researcher concluded that the use of concept mapping had a positive influence on understanding and applying the skills in a practical way. It is recommended to use this method in similar educational environments to help students with autism improve their learning and skill performance more effectively.